2020
DOI: 10.1038/s41467-020-18751-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic glucose-dependent insulinotropic polypeptide receptor (GIPR) agonism desensitizes adipocyte GIPR activity mimicking functional GIPR antagonism

Abstract: Antagonism or agonism of the glucose-dependent insulinotropic polypeptide (GIP) receptor (GIPR) prevents weight gain and leads to dramatic weight loss in combination with glucagon-like peptide-1 receptor agonists in preclinical models. Based on the genetic evidence supporting GIPR antagonism, we previously developed a mouse anti-murine GIPR antibody (muGIPR-Ab) that protected diet-induced obese (DIO) mice against body weight gain and improved multiple metabolic parameters. This work reconciles the similar prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 36 publications
3
72
0
Order By: Relevance
“…While loss-of-function studies indicate that GIP drives weight gain, when it comes to GIPR agonism and antagonism, compelling evidence paradoxically indicate that both approaches can reduce body weight, especially if combined with GLP-1 agonists (12,59). This paradox may reflect the partial agonistic activity of certain antagonists (60), compensatory relationship and overlapping signaling axes between GIPR and GLP-1R incretin receptors (59,61), as well as desensitization of GIPR achieved by chronic agonism (62). With respect to the latter, in cultured mouse or human preadipocytes, exposure to 1 mM dAla2-GIP for 24 h decreased cAMP response to subsequent GIPR stimulation up to 48 h (62), indicating that chronic GIPR agonism functionally mimics GIPR antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…While loss-of-function studies indicate that GIP drives weight gain, when it comes to GIPR agonism and antagonism, compelling evidence paradoxically indicate that both approaches can reduce body weight, especially if combined with GLP-1 agonists (12,59). This paradox may reflect the partial agonistic activity of certain antagonists (60), compensatory relationship and overlapping signaling axes between GIPR and GLP-1R incretin receptors (59,61), as well as desensitization of GIPR achieved by chronic agonism (62). With respect to the latter, in cultured mouse or human preadipocytes, exposure to 1 mM dAla2-GIP for 24 h decreased cAMP response to subsequent GIPR stimulation up to 48 h (62), indicating that chronic GIPR agonism functionally mimics GIPR antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…In a study published after Holst’s review, Killion et al . showed that chronic GIPR agonism desensitizes GIPR activity in primary adipocytes and functions like a GIPR antagonist, favouring the GIP receptor desensitisation scenario [ 60 ]. Importantly, GIP antagonists appear able to restore the cell surface expression of GIPR [ 61 ] and therefore possess the potential to restore endogenous GIP sensitivity, a function lost in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Confusingly, GIP receptor antagonism has also been shown to reduce food intake [ 112 ]. Recently, Killion et al showed that, in adipose tissue, prolonged GIP receptor agonism desensitizes receptor activity, hereby mimicking functional GIP receptor antagonism [ 113 ]. It has not yet been investigated whether this is the case also in neuronal cells expressing the GIP receptor, and further studies on this topic are warranted.…”
Section: The Role Of Glp-1 and Gip In Health And Under T2dm Conditmentioning
confidence: 99%
“…Interestingly, GIP receptor agonism has been reported to show results very similar to antagonist treatment [ 116 ]. As mentioned in the previous paragraph, this paradox could be explained through agonist-induced desensitization of the adipocyte GIP receptor [ 113 ]. Genome-wide studies have linked the GIPR locus to BMI, and diminished receptor activity is associated with decreased BMI [ 80 , 116 ].…”
Section: The Role Of Glp-1 and Gip In Health And Under T2dm Conditmentioning
confidence: 99%